Characteristics of Secang Jelly Drink as Functional Drink with the Addition of Red Ginger Extract for Antioxidant Source - Bevhia Moza Agusthi; Muhammad Fajri Romadhan (The University of Lampung, 2024)
Secang wood (Caesalpinia sappan L.) and red ginger can be used as alternative functional drinks in form of jelly drinks, due to the antioxidant properties contained in these two ingredients. In this study, we wanted to know the characteristics of secang jelly drinks with addition of red ginger extract at various concentrations. The research was conducted with ginger extract concentrations of 20% (J1), 25% (J2), 30% (J3), 35% (J4), and 40% (J5) executed completely random. The results of the research regarding the characteristics of secang jelly drink with the addition of red ginger extract have significant differences (p<0.05) for viscosity, pH value, antioxidant activity, and sensory as well as hedonic quality. The best treatment is obtained from red ginger extract concentration of 35% with an average viscosity of 986.7 cP, pH of 4.47, antioxidant activity with an IC50 value of 72.97 (strong), sensory score for aroma, texture, and taste is 5, hedonic quality score for aroma, texture, and taste is 4. This treatment also results in average total flavonoid content of 24.29 mg/100 g. No heavy metal contamination was found and total plate number was <102 colonies/mL. Keywords: Antioxidant, Functional drink, Jelly drink, red ginger, Secang woods.